FINANCIAL INSTABILITY HYPOTHESIS (FIH) OF MINSKY: CONTEXTUALIZING THE ROLES OF ISLAMIC COMMERCIAL AND SOCIAL FINANCE - Suharto, Ugi (Bank Indonesia, 2017)
The main subject of this paper is to discuss some issues in Minsky’s Financial Instability Hypothesis (FIH) and relate them with Islamic finance position in enhancing the stability of financial system. The methodology used in the paper is descriptive analysis. It describes a particular concept, namely the financial instability hypothesis and then analyses, applies and compares that concept with other concept, i.e. the Islamic finance concept. It is shown in the paper that Islamic finance, both in its commercial and social aspect, can play its role in stabilizing financial system. The significant contribution of the paper is by bringing together the hypothesis of Minsky with Islamic finance theory and practice. It should be stated here, however, that among the limitations of the paper is that the reference on Minsky’s point of view is mostly based on his brief article entitled “The Financial Instability Hypothesis” without referring to his vast writings on various topics directly or indirectly related to his notion of Financial Instability Hypothesis.